Komparasi Status Mutu Kimia Sungai Jagir Menggunakan Metode Indeks Pencemaran, STORET, dan BCWQI - Yuni Imroatul Mufida; Tuhu Agung Rachmanto (Yayasan Literasi Sains Indonesia, 2023)
Jagir River, which is a branch of the Brantas River, is often used as a waste disposal site by community activities. The residents’ activities caused the Jagir River was polluted and classified as class III where the parameters pH, COD, and TSS exceeded the quality standards. This is contrary to its designation as a tourism sector and river transportation. This research was conducted to analyze the parameter level of COD, BOD, and pH parameters at each sampling point as well as apply and compare the Pollution Index, STORET, and BCWQI methods. The sampling points in this study were divided into 4 location points with periodic monitoring, one week two sampling times, one day there were three sampling times, morning, afternoon and evening. The research results obtained, the parameters COD, BOD which exceed the established quality standards, namely Government Regulation Number 22 of 2021. The Pollution Index method has the highest value of 5.8 which is included in the